Exploring students' computer-supported collaborative argumentation with socio-scientific issues - CHEN, Wenli (Institutional Knowledge at Singapore Management University, 2024)
Background: This study examined the effect of computer-supported collaborative argumentation (CSCA) on secondary school students' understanding of socio-scientific issues (SSI). Engaging students in collaborative argumentation is known to help with deepening their understanding of SSI. Methods: In this study, a mixed-method design is used to investigate 84 students' collaborative argumentation processes and outcomes. The statistical analysis, epistemic network analysis and qualitative uptake analysis results showed that CSCA was effective in supporting secondary school students' evidence-based argumentation skills on SSI. Findings and Conclusion: Several cases were presented to show how students engaged in CSCA to explore meaningful learning opportunities and how CSCA helped students' learning on SSI. Implications: The findings provided insights for future innovative teaching and learning SSI in authentic classroom settings. What is already known about this topic Socio-scientific issues (SSI) serve as meaningful learning contexts for meaning-making and critical problem-solving. Computer-supported collaborative argumentation (CSCA) could help with students' SSI literacy. What this paper adds The effectiveness of a graph-based CSCA approach on students' SSI literacy. The patterns of students' engagement in CSCA on SSI. Implications for practice and/or policy With its shared working space, the graph-based CSCA platform could be an effective tool in supporting secondary school students' evidence-based argumentation skills on SSI. Students could benefit from appreciating peer idea exchange and offering constructive feedback to each other during the CSCA activities.